Long term effect of aspartame (Artificial sweetener) on membrane homeostatic imbalance and histopathology in the rat brain - Ashok, Iyaswamy; Sheeladevi, Rathinasamy; Wankhar, Dapkupar (Free Radicals and Antioxidants)
Background: The study focused to long-term effect of aspartame on membrane bound enzymes, oxidative stress markers and histopathology in brain regions of Wistar albino rats. Hence it is essential to observe whether the chronic aspartame administration (75 mg/kg b. wt) could release methanol and induce oxidative stress in the rat brain. Many reports are available on the use of aspartame as it releases methanol during metabolism. Methods: To mimic the human methanol metabolism the methotrexate treated rats were included to study the aspartame effects and the gamma glutamyl transpeptidase, NO, H2O2 and the membrane bound enzymes were observed in brain discrete regions. Results: There was a significant increase in all the parameters except with a significant decrease in membrane bound ATPases and creatine kinase. Luxol fast blue (LFB) staining were performed on brain cerebellum region which showed histopathological changes in aspartame treated MTX animals which showed a marked decrease in the density of white matter, intensity of staining and no. of stained neuron cells when compared to control and MTX control animals. Conclusion: Moreover, the increases in some of these enzymes were due to methanol per se and its metabolite may be responsible for the generation of oxidative stress and histopathology in brain regions.
Keywords: Aspartame; Membrane bound ATPases; Oxidative stress markers; Rat folate deficient model; Free radical